2020
DOI: 10.1074/jbc.ra119.011982
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1 reduces hyaluronan synthase 2 expression by inhibiting nuclear translocation of NF-κB and expression of the long-noncoding RNA HAS2–AS1

Abstract: Hyaluronan (HA) is one of the most prevalent glycosaminoglycans of the vascular extracellular matrix (ECM). Abnormal HA accumulation within blood vessel walls is associated with tissue inflammation and is prominent in most vascular pathological conditions such as atherosclerosis and restenosis. Hyaluronan synthase 2 (HAS2) is the main hyaluronan synthase enzyme involved in HA synthesis and uses cytosolic UDP-glucuronic acid and UDP-GlcNAc as substrates. The synthesis of UDP-glucuronic acid can alter the NAD+/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 96 publications
(99 reference statements)
4
34
0
Order By: Relevance
“…However, elucidating the mechanisms will still assist us in understanding how natural products interact with our proteome and how to enhance our health with natural products. Previous studies [ 51 , 52 , 53 , 54 , 55 , 56 ] and our results have demonstrated that resveratrol does interfere with the activities and alter the behavior of many proteins. It was proposed that the conventional one-drug-one-target paradigm cannot accurately describe the drug actions [ 57 ].…”
Section: Discussionsupporting
confidence: 67%
“…However, elucidating the mechanisms will still assist us in understanding how natural products interact with our proteome and how to enhance our health with natural products. Previous studies [ 51 , 52 , 53 , 54 , 55 , 56 ] and our results have demonstrated that resveratrol does interfere with the activities and alter the behavior of many proteins. It was proposed that the conventional one-drug-one-target paradigm cannot accurately describe the drug actions [ 57 ].…”
Section: Discussionsupporting
confidence: 67%
“…The combined treatment with tumor necrosis factor α (TNFα) and SIRT1 activators inhibited AoSMCs migration and immune cells adhesion to the HA-rich ECM. From a mechanistic point of view, we demonstrated that the activation of SIRT1 prevented NF-kB/p65 nuclear translocation and decreased the levels of HAS2-AS1, which in turn regulates HAS2 43 (Fig. 3).…”
Section: Regulation Of Has2 By Sirt1 and Has2-as1mentioning
confidence: 89%
“…1). As HA deposition is mainly due to HAS2, 43 the study of its regulation is fundamental to understand HA biology. HAS2 displays a multistep regulation that involves the action of different growth factors and cytokines.…”
Section: Ha Metabolizing Enzymesmentioning
confidence: 99%
“…20,21 Since high levels of UGDH activity have the potential to impact dynamic flux of NAD + /NADH ratios, it is also relevant to consider that UGDH impacts may be partially achieved through processes involving these redox cofactors. This is underscored by a recent report linking activation of the NAD + -dependent deacetylase, SIRT1, to the suppression of HA production via the transcriptional regulation of HAS2 (Caon et al 56 and reviewed in Caon et al 57 ).…”
Section: Post-translational Regulation Of Ugdh and Pg Productionmentioning
confidence: 99%